Lung Cancer Death Attributable to Long-Term Ambient Particulate Matter (PM2.5) Exposure in East Asian Countries During 1990–2019 - Liu, Xiaoxue; Mubarik, Sumaira; Wang, Fang; Yu, Yong; Wang, Yafeng; Shi, Fang; Wen, Haoyu; Yu, Chuanhua (Frontiers in Medicine, 2021)
Background: Ambient particulate matter is a public health concern in East Asia, which is contributing to a growing number of all-cause and cancer deaths. We aim to estimate lung cancer death attributable to ambient particulate matter (PM) < 2.5 μm (PM2.5) in East Asia countries. Methods: The attributable death rates of lung cancer were estimated based on the calculation of population attributable fraction. We performed joinpoint regression analysis and age-period-cohort (APC) model to estimate temporal trends of the attributable death to PM2.5. Results: In 2019, PM2.5 was estimated to have caused 42.2% (nearly 0.13 million) lung cancer deaths in East Asia men. During 1990-2019, the increase in age-standardized death rates of lung cancer attributable to PM2.5 was highest in China, which increased by 3.50% in males and 3.71% in females. The death rate caused by PM2.5 also significantly increased in Democratic People's Republic of Korea (2.16% in males; 3.06% in females). Joinpoint analysis showed that the rates generally increased in younger and older people in both Democratic People's Republic of Korea and Mongolia, while only increased in elder people in other countries. Age effect from APC analysis demonstrated the risk of lung cancer death attributable to PM2.5 generally increased from young to old age. Period effect indicated from 1994-1998 to 2019-2023 period, the risk continuously increased by 1.77, 1.68 and 1.72 times in China, Democratic People's Republic of Korea and Japan, respectively. Differently, the period risk decreased from 1999 to 2009 and subsequently increased from 2009 to 2019 in both Republic of Korea and Mongolia. Conclusions: The death rate of lung cancer attributable to PM2.5 is increasing in Democratic People's Republic of Korea, Mongolia and China. In East Asia, China is truly facing the highest attributable death during past decades. Period effect suggested a remarkably increasing risk of lung cancer death caused by PM2.5 in China, Democratic People's Republic of Korea and Japan during the long-term period. The governments should continuously concentrate on particulate matter pollution governance and improvement.